Uncovering the spatially uneven synergistic effects of China's enterprise-level industrial water pollutants reduction - Li, Jincheng; Jiang, Qingsong; Cai, Kaikui; Fu, Jiaxing; Liu, Yong; Chen, Dongni; Liu, Xiaoyu; Dai, Hancheng; Chen, Yihui; Chen, Yan (Resources, conservation and recycling, 2023)
•China Industrial Economic and Pollutant Emission data (CIEPE) with 1.28 million individual enterprise data.•The reduction of pollutants loading at different stages has synergic effects.•The response between national development strategies implementation and pollutants loading reduction has a hysteresis effect.•Three risks in China's industrial pollution control should be paid more attention. China has made great efforts in industrial pollution control, but for the different industrial sectors under various development stages, it is not so clear whether there is synergistic effects among them, and how it changes with the environmental policies. This study filled this knowledge gap by comiling the China Industrial Economic and Pollutant Emission data (WatSim-CIEPE) using 1.28 million individual enterprise data. The results demonstrated a power function decreasing trend for the emission per unit output value. The load reduction at different stages had synergic effects, and coastal cities reached the inflection point earlier. There is a completely opposite pattern between pollutant emission and GIOV in spatial evolution, mainly because the chemical and metal sectors with high pollutant emissions and low GIOV migrated to western China. The year gap between the implementation of the national development strategy and the break-point of gravity center variation of GIOV indicates a hysteresis effect for the influence of development policies. There may be three risks in China's industrial pollution control: (a) NH pollution gets serious in the western regions; (b) the food sector may become a new dominant pollution source; (c) the imbalance between industrial development and pollution control may further aggravate.